Combining single-cell and transcriptomic analysis revealed the immunomodulatory effect of GOT2 on a glutamine-dependent manner in cutaneous melanoma - Song, Lebin; Wei, Xiyi; Zhang, Xi; Lu, Yan (Frontiers in Pharmacology, 2023)
Background: Repro¬gramming in glutamine metabolism is a hallmark of cancers, while its role in cutaneous melanoma (CM) has not been studied at great length. Methods: Here, we constructed a glutamine metabolism-related prognostic signature in CM with a variety of bioinformatics methods according to the glutamine metabolism regulatory molecules. Moreover, experimental verification was carried out for the key gene. Results: We have identified two subgroups of CM patients, each with different prognoses, immune characteristics, and genetic mutations. GOT2 was the most concerned key gene among the model genes. We verified its role in promoting tumor cell proliferation by CCK-8 and clone formation assays. Conclusion: Our study cast new light on the prognosis of CM, and the internal mechanism regulating glutamine metabolism of GOT2 may provide a new avenue for treating the CM disease precisely.